(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In general 26 taxa of Rotifera, 8 taxa Cladocera and 3 taxa Copepoda group were found in the Daugava River in sampling site- Jēkabpils in 2019, but 25 taxa of Rotifera, 6 taxa Cladocera and 2 taxa Copepoda group were found in the Daugava River in sampling site- Veczeļķi in 2019. In contrast, 26 taxa of Rotifera, 7 taxa Cladocera and 1 taxon Copepoda group were found in the Daugava River in sampling site- Jēkabpils in 2020, and 23 taxa of Rotifera, 1 taxa Cladocera group were found in the Daugava River in sampling site- Veczeļķi in 2020. 28 taxa of Rotifera, 13 taxa Cladocera and 4 taxon Copepoda group were found in the Pļaviņas Reservoir (sampling site- Gostiņi) in 2019, and 25 taxa of Rotifera, 7 taxa Cladocera group and 2 taxon Copepoda group were found in 2020. In the Daugava River in sampling site- Jēkabpils and Veczeļķi the highest percentage of Rotifera taxa were Synchaeta sp., Keratella cochlearis, Brachionus calyciflorus, Brachionus quadridentatus, Euchlanis sp., Polyarthra sp., which were typical species of the Daugava. Cladocera and Copepoda compared with Rotifera have very small percentage of representatives. Rotifera taxa of Pļaviņas Reservoir the highest percentage are Synchaeta sp., Brachionus calyciflorus, Keratella cochlearis, Keratella quadrata, Polyarthra sp. and Asplanchna priodonta. From Cladocera here were found typical of lake zooplankton taxa i.e Bosmina longirostris, Chydorus ovalis, Diaphanosoma brachyurum, Ceriodaphnia sp. Water temperature in the upper layer of the Daugava River and of the Plavinas Reservoir were 22 0C, the dissolved oxygen content 12 mg/l and chlorophyll α concentration 4 μg/l.